Workbook for Milady U Faculty Development - Solomon, Amy (Delmar Thomson Learning, 2007)
Module 12 suggests a variety ways to create an innovative learning environment for the adult learner. Both easy to implement and high technology ideas are discussed. The areas include creating innovative classroom facilities, conducting innovative learning activities, including more collaboration in teaching, and using instructional technology both for instruction and communication. It also includes: section 1: an overview of innovation in higher education; section 2: innovation in classroom facilities; section 3: innovation in learning activities; section 4: collaborative learning; and section 5: innovative learning technologies